Genome-wide identification and characterization of abiotic stress responsive GRAS family genes in oat (Avena sativa) - Jing Pan; Qingping Zhou; Hui Wang; Youjun Chen; Zhiqiang Wang; Junchao Zhang (PeerJ, 2023)
Background GRAS transcription factors play a variety of functions in plant growth and development and are named after the first three transcription factors GAI (GIBBERRELLICACIDINSENSITIVE), RGA (REPRESSOROFGAI), and SCR (SCARECROW) found in this family. Oat (Avena sativa) is one of the most important forage grasses in the world. However, there are few reports on the GRAS gene family in oat. Methods In order to understand the information and expression pattern of oat GRAS family members, we identified the GRAS members and analyzed their phylogenetic relationship, gene structure, and expression pattern in oat by bioinformatics technology. Results The results showed that the oat GRAS family consists of 30 members, and most of the AsGRAS proteins were neutral or acidic proteins. The phylogenetic tree divided the oat GRAS members into four subfamilies, and each subfamily has different conservative domains and functions. Chromosome location analysis suggested that 30 GRAS genes were unevenly distributed on five chromosomes of oat. The results of real-time quantitative reverse transcription-PCR (qRT-PCR) showed that some AsGRAS genes (AsGRAS12, AsGRAS14, AsGRAS21, and AsGRAS24) were all up-regulated with increasing stress treatment time.The results of this study provide a theoretical basis for further research into the corresponding stress of oat. Therefore, further studies concentrating on these AsGRAS genes might reveal the many roles played by GRAS genes in oat.